Body Composition Characteristics of Community-Dwelling Older Adults With Dynapenia - Jung, Hungu; Tanaka, Shigeharu; Tanaka, Ryo (Frontiers in Nutrition, 2022)
This study aimed to determine the differences in muscle and fat masses of the arm and leg between older adults with dynapenia, sarcopenia, or presarcopenia and normal individuals. The percent body fat, lean body mass, and skeletal mass index were measured with bioelectrical impedance analysis. Muscle function was evaluated using grip strength and walking speed. Participants were classified into four categories. Dynapenia was defined as low muscle function with normal muscle mass. Sarcopenia was defined as the presence of both low muscle mass and low muscle function. Presarcopenia was defined as low muscle mass with normal muscle function. Control was defined as normal muscle mass and function. Multivariate analyses of variance were performed separately for women and men to test the main effect of sarcopenia category on body composition. Among the 356 enrolled participants, 270 were women, and 86 were men. In older women, the dynapenia and sarcopenia groups had significantly less muscle mass in the leg than the control group. In older men, the dynapenia group demonstrated a higher body fat mass in the leg than the control group. These results suggest that different strategies are necessary to prevent dynapenia in women and men.